Smoking cessation support - the new or old role of pharmacists - Milošević Georgiev, Andrijana (Archives of Pharmacy, 2022)
Pharmacies are the most represented health institutions in a community. Some of their numerous benefits for public health activities are longer working hours and possibility to get advice without making an appointment. An increasing number of countries has recently become actively involved in the promotion of public health services in pharmacies. A review of the papers shows that pharmacists feel more comfortable in providing drug-related than public health-related services. In the United Kingdom, smoking cessation activities are the most common public health activity of pharmacists. Smoking is a difficult form of addiction. Quitting smoking is a big challenge. Many states allow pharmacists to initiate therapy or assess the success of cessation and monitor for adverse reactions. According to pharmacy students in Serbia, the pharmacy is a place where public health services should be provided (98.7%), while 59.7% of respondents believe that smoking cessation services should also be implemented there. The general public (80.3%) strongly agrees that public health activities should be an integral part of pharmacy services. The general population supports the smoking cessation service in the percentage of 36.7%, while pharmacists support it in 49.2%. The views of pharmacy students, the general public and pharmacists point to a positive attitude towards the new and modern model of pharmacists, which certainly includes public health services. Before the pilot implementation of these pharmaceutical services in pharmacies, the main obstacles should be identified and overcome.